2010
DOI: 10.1523/jneurosci.5538-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Enhances Amygdala-Dependent, Socially Reinforced Learning and Emotional Empathy in Humans

Abstract: Oxytocin (OT) is becoming increasingly established as a prosocial neuropeptide in humans with therapeutic potential in treatment of social, cognitive, and mood disorders. However, the potential of OT as a general facilitator of human learning and empathy is unclear. The current double-blind experiments on healthy adult male volunteers investigated first whether treatment with intranasal OT enhanced learning performance on a feedback-guided item-category association task where either social (smiling and angry f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

52
525
10
18

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(605 citation statements)
references
References 73 publications
52
525
10
18
Order By: Relevance
“…As of yet, however, there has been no data-driven explanation as to why PTSD affects victims of various types of traumas at differential rates: intentional acts of interpersonal violence, in particular sexual assault, lead to PTSD at far higher rates than do accidents or disasters (Cantor, 2009). There is evidence at least in females that interpersonal stress is linked to heightened endogenous OXT release (Taylor et al, 2010), and we have previously shown that heightened OXT increases learning in a social context (Hurlemann et al, 2010). Taken together with the results of the current study, we speculate that vulnerability for SAD and socially elicited PTSD could be associated with OXT's enhanced adaptation to social situations as discussed above.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As of yet, however, there has been no data-driven explanation as to why PTSD affects victims of various types of traumas at differential rates: intentional acts of interpersonal violence, in particular sexual assault, lead to PTSD at far higher rates than do accidents or disasters (Cantor, 2009). There is evidence at least in females that interpersonal stress is linked to heightened endogenous OXT release (Taylor et al, 2010), and we have previously shown that heightened OXT increases learning in a social context (Hurlemann et al, 2010). Taken together with the results of the current study, we speculate that vulnerability for SAD and socially elicited PTSD could be associated with OXT's enhanced adaptation to social situations as discussed above.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, in accordance with previous findings (Rash et al, 2014), OXT attenuated both neural and psychophysiological responses to the aversive electric shock. Thus an OXT-induced augmentation of fear conditioning cannot be attributed to increased pain responses but appears to be mediated by improved learning (Hurlemann et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since oxytocin is also considered as a key mediator of social cognition in humans [37] and this effect has been postulated to specifically involve the OT system in the Amy [38], the OTR upregulation observed here might also be associated with a possible nicotine regulation of cognition through an OTR-dependent mechanism. However, this hypothesis needs to be further investigated.…”
Section: Discussionmentioning
confidence: 71%
“…In animal models administration of oxytocin increases maternal behaviours including grooming, nesting, and pair bond formation [22][23][24] . In humans, administration of oxytocin to healthy adults increases trust and cooperative behaviours 25,26 , emotional empathy 27 , facial expression recognition [28][29][30] , and theory of mind skills 31 . In addition, oxytocin administration to autistic patients facilitates social information processing and decreases repetitive behaviours 32,33 .…”
mentioning
confidence: 99%